CHILD PROTECTION AND JUVENILE JUSTICE: LEGAL ISSUES IN BANGLADESH AND MALAYSIA (UUM Journal of Legal Studies, 2024)
Child protection and juvenile justice are emerging issues and a major concern for nations across the globe. Considering the importance of child protection, different nations in the world have also given attention to reducing child delinquency by amending their laws on children. Bangladesh and Malaysia have ratified the UN Convention on the Rights of the Child (UNCRC) 1989 and incorporated its principles into their domestic legal framework for child-friendly care and protection of juvenile offenders. Since 2013, there have been many new concepts developed on this issue in the legal systems of both countries. The government of Bangladesh has enacted the Children Act 2013 by replacing the previous Children Act 1974. As a result, Bangladesh can now legally safeguard children’s best interests more effectively. The Malaysian government amended the Child Act 2001 and introduced the Child (Amendment) Act 2016 to protect children and establish institutional treatments for juvenile offenders. The government has also legislated the Sexual Offences Against Children Act 2017 to reduce delinquency. As a result, the child protection and justice systems in both countries have developed new dimensions, as well as preventing the abuse of the vulnerabilities of detained children during pandemic times. The present study analyses the major changes in the juvenile justice process in both countries, especially the protection of children as per the domestic legal framework and at the same time guided by international legal standards. The present study has a qualitative research design and uses content analysis to identify, analyze, and synthesize the content of child-related laws. The findings will be valuable to policymakers, as they point to the need to strengthen the existing legal framework for better child protection within the justice systems of both Bangladesh and Malaysia.